Mengurai Narasi Bertumbuh Dalam Kristus Dari Potret Kaum Muda Pentakostal Masa Kini - Yakobus, Yakobus (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2025)
Growing is a natural stage that must be passed by every living creature, including humans. Paul considered that in order to maximize their function as God's instruments, it is a must for believers to grow in Christ. This article attempts to describe growing in Christ from the portrait of today's Pentecostal youth. The method used in working on this article is qualitative narrative and literature review. This article narrates various examples of growing in God that the Bible records, narrates growing in Christ according to Colossians 2, and the portrait that Pentecostal youth narrate about growing in Christ today. It is concluded that Pentecostal youth portray growing in Christ as meaning diligent in worship, harmony between words and deeds, a consistent life in following God, and being an example for other believers.AbstrakBertumbuh merupakan tahapan alamiah yang mesti dilewati oleh setiap mahluk hidup tak terkecuali manusia. Paulus menilai bahwa untuk maksimal melaksanakan fungsinya sebagai alat Tuhan, bagi orang percaya adalah sebuah keharusan untuk bertumbuh dalam Kristus. Artikel ini berupaya untuk menjabarkan bertumbuh dalam Kristus dari potret kaum muda pentakostal masa kini. Metode yang digunakan dalam mengerjakan artikel ini adalah kualitatif naratif dan kajian literatur. Artikel ini menarasikan berbagai contoh bertumbuh dalam Allah yang Alkitab catat, menarasikan bertumbuh dalam Kristus menurut Kolose 2, serta potret yang kaum muda pentakostal narasikan tentang bertumbuh dalam Kristus pada masa kini. Disimpulkan bahwa kaum muda pentakostal memotret bertumbuh dalam Kristus itu berarti rajin beribadah, selaras antara perkataan dan perbuatan, kehidupan yang konsisten dalam mengiring Tuhan, dan menjadi contoh untuk orang percaya lain.